2010
DOI: 10.1270/jsbbs.60.243
|View full text |Cite
|
Sign up to set email alerts
|

Transgressive segregation of isoflavone contents under the control of four QTLs in a cross between distantly related soybean varieties

Abstract: Soybean (Glycine max (L) Merr.) isoflavones have attracted considerable attention for their diverse effects on human health. To determine the genetic factors that contribute to the high isoflavone contents of the soybean varieties 'Peking' and 'Tamahomare', we conducted QTL analyses for the total content of daidzein derivatives (DAC), genistein derivatives (GEC) and glycitein derivatives (GLC), and for the total content of isoflavones (TIC) using recombinant inbred lines (RILs) derived from the cross between '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
(45 reference statements)
1
13
0
2
Order By: Relevance
“…We identified a QTL associated with the contents of Gly and M_Gly on chromosome Gm11. Other major QTLs at this locus explaining 40% to 50% of variance were also reported in crosses between 'Essex' and 'Forrest' (Kassem et al 2004, Meksem et al 2001 and between 'Peking' and 'Tamahomare' (Yoshikawa et al 2010). Genomewide asso ciation analysis detected significant association with gly of homologous genes (Mameda et al 2018).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We identified a QTL associated with the contents of Gly and M_Gly on chromosome Gm11. Other major QTLs at this locus explaining 40% to 50% of variance were also reported in crosses between 'Essex' and 'Forrest' (Kassem et al 2004, Meksem et al 2001 and between 'Peking' and 'Tamahomare' (Yoshikawa et al 2010). Genomewide asso ciation analysis detected significant association with gly of homologous genes (Mameda et al 2018).…”
Section: Discussionmentioning
confidence: 56%
“…Isoflavone contents in soybean seeds are also affected by environmental factors, such as tempera ture during seed maturation, soil, and cultivation conditions (Hoeck et al 2000, Rasolohery et al 2008, Tsukamoto et al 1995. Multiple environmental evaluations with the same population indicated that the heritability of each isoflavone component is 0.6 to >0.9 (Yoshikawa et al 2010). The com parison of F6H expression among several lines with high, low, and null glycitein contents revealed a putative associa tion with accumulation of glycitein (Artigot et al 2013).…”
Section: Plant Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…The current QTLs are in accordance with the results of previous measurements of isoflavonoid contents of soybean seeds. qDZS1 on Chr.8, qGNS1 on Chr.6 and qGNS3 on Chr.18 have been reported by Yoshikawa and colleagues [ 29 ], while qDZS3 and qGNS2 have been reported by Wang and colleagues [ 30 ]. This indicates that the isoflavonoid contents in seeds and their secretions from roots of soybean are regulated by the same genetic factors.…”
Section: Discussionmentioning
confidence: 88%
“…This indicates that the isoflavonoid contents in seeds and their secretions from roots of soybean are regulated by the same genetic factors. Daidzein and genistein levels in seeds are not very different among Peking, Tamahomare and the RILs [ 29 ]. In the roots of RIL plants, however, we found that daidzein secretions were nearly 100 times greater than genistein secretions in the early stage of growth (seven days after sowing).…”
Section: Discussionmentioning
confidence: 99%